24.4k views
19 votes
Simplify the following expression

Simplifying expressions
8th grade math
Algebra 1

Can someone explain why
(-5k^2m)(2km)^4(3km^4)^2
——————————————
k^2m^3
Simplifies to -720k^6m^10

But 3m/m^4 simplifies to 3/m^2
Even though their both fractions how come only one stays a fraction? What’s the difference so I can figure out in the future?

User TanjiroLL
by
4.7k points

1 Answer

7 votes

Answer:

1.
((-5k^(2)m)(2km)^(4) (3km^(4)) ^(2))/(k^(2)m^(3)) = -720
k^(6)m^(10)

2.
(3m)/(m^(4) ) =
(3)/(m^(3) ) (or 3
m^(-3))

Explanation:

1. The given expression is:


((-5k^(2)m)(2km)^(4) (3km^(4)) ^(2))/(k^(2)m^(3))

With respect to the principle of exponential, we have;


((-5k^(2)m)(2^(4)k^(4) m^(4))(3^(2)k^(2)m^(8)))/(k^(2) m^(3) ) =
((-5k^(2)m)(16k^(4) m^(4))(9k^(2)m^(8) )/(k^(2)m^(3) )

Applying the law of indices,

=
((-5*16*9)(k^(2+4+2))(m^(1+4+8)) )/(k^(2) m^(3) )

=
(-720k^(8) m^(13) )/(k^(2)m^(3) )

= -720
k^(8)m^(13) x
k^(-2) m^(-3)

= -720
k^(8-2) m^(13-3)

= -720
k^(6)m^(10)

2.
(3m)/(m^(4) )

divide the numerator and denominator with common factor m,

=
(3)/(m^(3) )

This can not be simplified further since there are no more common factors, so that;


(3m)/(m^(4) ) =
(3)/(m^(3) ) (or 3
m^(-3))

User Rogeriojlle
by
4.7k points